The Prospect of China’s Renewable Automotive Industry Upon Shrinking Subsidies - Qiu, Lin-Shu; Yang, Dong-Xiao; Hong, Kai-Rong; Wu, Wei-Ping; Zeng, Wei-Kang (Frontiers in Energy Research, 2021)
The increased emissions from road traffic resulting from the increase in car ownership have put enormous pressure on China's environmental problems. In order to solve this problem, the Chinese government attaches great importance to the development of the new energy vehicle industry. This paper summarizes the incentive policies of China's new energy vehicle industry. Through sorting out the incentive policy system of the new energy vehicle industry, we find that the Chinese government's promotion policy for the new energy vehicle industry is a process of gradual transformation from government-led to market-led. In this process, with the decrease of the subsidy amount, it is bound to cause a huge impact on the new energy vehicle industry.